2020
DOI: 10.1186/s12889-020-09486-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial access inequities and childhood immunisation uptake in Kenya

Abstract: Background Poor access to immunisation services remains a major barrier to achieving equity and expanding vaccination coverage in many sub-Saharan African countries. In Kenya, the extent to which spatial access affects immunisation coverage is not well understood. The aim of this study was to quantify spatial accessibility to immunising health facilities and determine its influence on immunisation uptake in Kenya while controlling for potential confounders. Methods Spatial databases of immunising facilities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 40 publications
1
83
1
Order By: Relevance
“…106 110 Healthcare utilisation rates are low due to poor infrastructure and limited geographical access, conflict and insecurity hence low immunisation rates and use of modern contraceptives. 71 73 74 101 111 However, in this region, religion and cultural beliefs might be a stronger determinant of contraception use in comparison to poverty and lack of access. [112][113][114] In view of historical and economic similarities between regions in Kenya, six economic blocs were formed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…106 110 Healthcare utilisation rates are low due to poor infrastructure and limited geographical access, conflict and insecurity hence low immunisation rates and use of modern contraceptives. 71 73 74 101 111 However, in this region, religion and cultural beliefs might be a stronger determinant of contraception use in comparison to poverty and lack of access. [112][113][114] In view of historical and economic similarities between regions in Kenya, six economic blocs were formed.…”
Section: Discussionmentioning
confidence: 99%
“…12 68-70 Demand and supply challenges such as spatial access, health workforce, stockouts, cost of transportation and cold chain could also have hampered vaccination uptake especially in Northern Kenya where coverage was lower. [70][71][72][73][74][75] Child and maternal survival interventions such as supplements have been delivered through the Malezi Bora initiative since 2007, a health facility-based delivery system migrating away from the previous door-to-door approach to reduce implementation cost. 35 This might have also encouraged the uptake of immunisations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The institutional level describes the roles that characteristics and operations of social institutions, including health facilities and their health workers, play in shaping health care decision-making (11). Studies have shown that availability and access to health care facilities signi cantly affect care-seeking behavior and utilization of health services (32)(33)(34)(35). In addition, patient-health care worker communication signi cantly impacts healthcare utilization, decision-making, acceptance of recommended health behaviors, and medical management (36)(37)(38).…”
Section: Institutional-level Factorsmentioning
confidence: 99%